2015
DOI: 10.1007/s00128-015-1608-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Endosulfan to the Non-target Organisms Hyalella curvispina and Cnesterodon decemmaculatus

Abstract: Pesticide consumption in Argentina has steadily increased over the last two decades, while one of these compounds, namely endosulfan, is commonly found in environmental samples. Also the fish Cnesterodon decemmaculatus and the amphipod Hyalella curvispina are widely distributed in agricultural areas of southern South America. The aim of the present contribution was therefore to determine the acute toxicity of endosulfan to both organisms, and compare it with species sensitivity distributions (SSD) and measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In recent years, the amphipod Hyalella curvispina (Hc), widely distributed in South America, has been used as a test organism in ecotoxicological assessments. This amphipod is part of the native fauna and has been used in laboratory bioassays to assess sensitivity to different toxic agents (Giusto et al, 2012, Peluso et al, 2013a, Anguiano et al, 2014, Mugni et al, 2015, in assessments of environmental samples (Di Marzio et al, 1999, Míguez et al, 2012, Peluso et al, 2013a, Peluso et al, 2013b, Giusto et al, 2014, Peluso et al, 2016, Mac Loughlin et al, 2017, and as a test organism in certain field evaluations (Graça et al, 2002, Jergentz et al, 2004, Venturino et al, 2007, Mugni et al, 2012, Mugni et al, 2016. Although other species of amphibians have been used in bioassays as potential model indicators (Natale et al, 2006, Salgado Costa, 2016; only one protocol in Argentina, under the acronym of ANFITOX, has been found to be applicable to embryos and larvae of amphibians (Herkovits and Pérez-Coll, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the amphipod Hyalella curvispina (Hc), widely distributed in South America, has been used as a test organism in ecotoxicological assessments. This amphipod is part of the native fauna and has been used in laboratory bioassays to assess sensitivity to different toxic agents (Giusto et al, 2012, Peluso et al, 2013a, Anguiano et al, 2014, Mugni et al, 2015, in assessments of environmental samples (Di Marzio et al, 1999, Míguez et al, 2012, Peluso et al, 2013a, Peluso et al, 2013b, Giusto et al, 2014, Peluso et al, 2016, Mac Loughlin et al, 2017, and as a test organism in certain field evaluations (Graça et al, 2002, Jergentz et al, 2004, Venturino et al, 2007, Mugni et al, 2012, Mugni et al, 2016. Although other species of amphibians have been used in bioassays as potential model indicators (Natale et al, 2006, Salgado Costa, 2016; only one protocol in Argentina, under the acronym of ANFITOX, has been found to be applicable to embryos and larvae of amphibians (Herkovits and Pérez-Coll, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The average body weight of the specimens used throughout the experiments was 0.20 70.1 g, and the mean body length was 25.5 72.2 mm. For each experimental point, 10 randomly selected specimens were maintained in a 1 L glass container according recommendations reported elsewhere (Mugni et al, 2016;Ruiz de Arcaute et al, 2014;Vera-Candioti et al, 2010, 2013a, 2013b, 2013c. To determine the concentrations used in the acute toxicity tests, preliminary assays were performed according the recommendations proposed by the U.S. USEPA (2002).…”
Section: Determination Of Lc 50mentioning
confidence: 99%
“…Several studies have shown that C. decemmaculatus, the ten spotted live-bearer, is a valid bioindicator of environmental quality in assessing the lethal and sublethal effects of several pesticides, e.g., pirimicarb (Vera-Candioti et al 2010, 2013b, endosulfan (Mugni et al 2012(Mugni et al , 2015, cypermethrin (Carriquiriborde et al 2007;Mugni et al 2012), glyphosate (Vera-Candioti et al 2013a, 2013b, chlorpyrifos (Mugni et al 2012;Vera-Candioti et al 2013b), 2,4-D (Ruiz de Arcaute et al 2016, 2018a and dicamba (Ruiz de Arcaute et al 2014aArcaute et al , 2018a, among others.…”
Section: Introductionmentioning
confidence: 99%